2019
DOI: 10.1182/blood-2019-132105
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Sequencing Reveals Evolution of Tumor Heterogeneity of Acute Myeloid Leukemia on Quizartinib

Abstract: Introduction: Clonal selection occurring under the selective pressure of Fms-like tyrosine kinase 3 (FLT3) tyrosine kinase inhibitor (TKI) therapy is not fully understood. To date, the most common mutations found at the time of resistance to potent and selective type II FLT3 TKIs, like quizartinib, are on-target kinase domain (KD) mutations. Activating RAS pathway mutations are a common mechanism of resistance to type I FLT3 TKIs (McMahon et al., 2019 and Zhang et al., 2019). Changes in the acute myeloid leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Serial single-cell sequencing confirmed early selection for RAS- mutant subclones under gilteritinib pressure ( 63 ). In an analysis of paired pre- and post-treatment samples of patients treated with quizartinib, NRAS development was similarly noted at relapse; furthermore, single cell sequencing confirmed these distinct subclones existed in small populations prior to therapy and expanded under FLT3 inhibition ( 66 ).…”
Section: Ongoing Questions and Controversiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Serial single-cell sequencing confirmed early selection for RAS- mutant subclones under gilteritinib pressure ( 63 ). In an analysis of paired pre- and post-treatment samples of patients treated with quizartinib, NRAS development was similarly noted at relapse; furthermore, single cell sequencing confirmed these distinct subclones existed in small populations prior to therapy and expanded under FLT3 inhibition ( 66 ).…”
Section: Ongoing Questions and Controversiesmentioning
confidence: 95%
“…In most cases, on-target mutations are not detected prior to FLT3 inhibitor treatment ( 65 ). In a recent study of 11 patients treated with quizartinib monotherapy, single-cell sequencing revealed 7/11 patients developed KD mutations at relapse and no patients had these mutations prior to FLT3 inhibition, suggesting TK mutations typically evolve de novo ( 66 ) or exist at levels undetectable by current sequencing methods.…”
Section: Resistance To Flt3 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonal evolution at relapse was also found to be impacted by therapeutic selective pressures in patients receiving targeted therapy 10 . Leukaemic relapses post‐gilteritinib and ‐quizartinib exhibited different combinations of mutational changes; FLT3‐ITD mutational loss, additional FLT3 mutation gain and/or addition of entirely new gene mutations often in the Ras/mitogen‐activated protein kinase (MAPK) pathway were observed at relapse 12,13 …”
Section: Clonal Evolution and Selection Towards Resistant Clone Survivalmentioning
confidence: 99%
“…10 Leukaemic relapses post-gilteritinib and -quizartinib exhibited different combinations of mutational changes; FLT3-ITD mutational loss, additional FLT3 mutation gain and/ or addition of entirely new gene mutations often in the Ras/ mitogen-activated protein kinase (MAPK) pathway were observed at relapse. 12,13 Clonal evolution at relapse following allogeneic stem cell transplant…”
Section: Clona L Evolu Tion a N D Se L Ec Tion Towa R Ds R E Sista N ...mentioning
confidence: 99%